CLINICAL AND RADIOLOGICAL ASPECTS OF REVERSIBLE AND IRREVERSIBLE PULPITIS OF PRIMARY TEETH - Holubieva, Inna; Ostapko, Olena; Nemyrovych, Julia; Gurianov, Vitaliy; Boichenko, Mariia; Illienko, Natalia (Eastern Ukrainian Medical Journal, 2024)
The development of clinical guidelines and standards for the provision of medical dental care to the pediatric population in Ukraine is based on the principles of evidence-based medicine, modern international classifications and is consistent with the generally accepted worldwide diagnostic terminology of the main dental diseases. Therefore, the purpose of the study was to determine the frequency, clinical and radiological characteristics, diagnostic criterias for reversible and irreversible pulpitis of primary teeth. Materials and methods: 328 children aged 3 to 7 years were examined at the Dental Medical Center of the Bogomolets National Medical University. All participants underwent a clinical examination of the condition of the hard tissues in primary teeth, a cold test, radiological examination of the carious lesion depth and an intraoperative assessment of bleeding from the pulp. Results: A high prevalence (92.7%) and mostly asymptomatic course (83.2%) of primary teeth pulpitis in children aged 3 to 7 years was revealed. The frequency of irreversible pulpitis was 2.1 times higher than the similar indicator of reversible pulpitis (p<0.001). From the age of 5, a statistically significant decrease in the number of primary teeth with reversible pulpitis was observed, in parallel with the increase of this indicator in case of irreversible inflammation of the pulp. Lesions of molars were registered in the vast majority of cases compared to the anterior teeth. Most often, pulpitis was diagnosed in the first primary molars of the lower jaw (p<0.01). Cold test was informative in cooperative children (25.7%), mostly 6-7 years old. Significant differences in the radiological depth of carious lesions in reversible and irreversible pulpitis of primary teeth were revealed. Intraoperative assessment of bleeding and achievement of hemostasis after vital pulpotomy indicated the absence of the radicular pulp inflammation. Conclusions: Clinical evaluation of the depth of carious defects does not allow making determination the thickness of the dentin lesion and the proximity to the pulp, except in cases of its carious exposure. Cold test for the sensitivity of the pulp in preschool age was not accurate enough due to the high probability of false positive answers. The most informative methods of preoperative diagnosis of pulpitis include radiological examination, which characterizes the depth of the carious lesion and its proximity to the pulp. Reliable radiological signs of irreversible pulpitis were connection with the pulp chamber, destruction of the cortical plate of the alveolus, translucency of the spongy bone in the furcation and periapical areas. However, radiological diagnostics does not reflect the prevalence of inflammation in the pulp. Therefore, the intraoperative assessment of bleeding and the achievement of hemostasis after vital pulpotomy are decisive criteria for the absence of inflammation in radicular pulp and the possibility of its preservation. So, differential diagnosis of reversible and irreversible pulpitis of primary teeth should be based on a combination of preoperative and operative research methods. Due to the high prevalence of pulpitis in children aged 6-7 years, primary prevention of early childhood caries should be the primary task of pediatric dentistry.